2016
DOI: 10.3390/nu8020038
|View full text |Cite
|
Sign up to set email alerts
|

Tucum-Do-Cerrado (Bactris setosa Mart.) Consumption Modulates Iron Homeostasis and Prevents Iron-Induced Oxidative Stress in the Rat Liver

Abstract: This study investigated the effect of tucum-do-cerrado consumption in the oxidative status of iron-supplemented rats. Four groups of rats were treated: Control (AIN-93G), Tuc (AIN-93G added of tucum-do-cerrado), Fe (AIN-93G iron-enriched), or TucFe (AIN-93G with tucum-do-cerrado and iron-enriched) diet, for 30 days. Iron-enriched diet increased serum, liver, spleen, and intestine iron levels; transferrin saturation; liver lipid oxidation; mRNA levels of hepatic Hamp and Bmp6, and Nrf2 in the intestine. Tucum-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
0
23
1
2
Order By: Relevance
“…Interestingly, flavonoid glycosides, derived from apigenin, present in beet stalks and leaves may have acted as natural exogenous antioxidants, reducing or minimizing the oxidative stress in mice that were fed on a high-fat diet, similarly to the observations of other studies [ 40 , 41 , 42 ]. This effect may be due to the antioxidant activity of polyphenols present in fruits and vegetables, which may reduce the requirement for antioxidant enzymatic function by up-regulating Nrf 2-dependent antioxidant enzymes [ 43 ]. As a consequence, there was no alteration in the activities of antioxidant enzymes, such as GPx [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, flavonoid glycosides, derived from apigenin, present in beet stalks and leaves may have acted as natural exogenous antioxidants, reducing or minimizing the oxidative stress in mice that were fed on a high-fat diet, similarly to the observations of other studies [ 40 , 41 , 42 ]. This effect may be due to the antioxidant activity of polyphenols present in fruits and vegetables, which may reduce the requirement for antioxidant enzymatic function by up-regulating Nrf 2-dependent antioxidant enzymes [ 43 ]. As a consequence, there was no alteration in the activities of antioxidant enzymes, such as GPx [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be due to the antioxidant activity of polyphenols present in fruits and vegetables, which may reduce the requirement for antioxidant enzymatic function by up-regulating Nrf 2-dependent antioxidant enzymes [ 43 ]. As a consequence, there was no alteration in the activities of antioxidant enzymes, such as GPx [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerrado plant species are edible antioxidant-rich plants commonly found in Brazil. Among these species, the extract of the fruit of the tucum-do-cerrado plant (a fruit with a purple skin, whitish pulp, and a large seed) was shown to attenuate iron-induced increases in serum and tissue iron levels, transferrin saturation, and lipid oxidation (by increasing the expression of intestinal Nrf2 and hepatic hepcidin, ferritin, heme oxygenase 1 [Hmox1], NADPH dehydrogenase quinone 1 [Nqo1], Nrf2, and Bmp6), ultimately increasing the activity of antioxidant enzymes, including catalase, glutathione reductase, and GPx [ 82 ]. The authors found a general correlation between reduced oxidative damage and iron availability.…”
Section: Bioactive Compounds That Regulate Oxidative Stress and Irmentioning
confidence: 99%
“…Tucum-do-cerrado ( Bactris setosa Mart. ), a Brazilian savanna fruit, has a high content of different phytochemical compounds such as cyanidin-derivatives, epicatechin, catechin, piceatannol, quercetin, and all- trans -lutein, mainly found in the peel [ 25 , 27 ] and a high antioxidant potential in vitro and in vivo [ 28 , 29 , 30 ]; however, many other potential biological effects still need to be investigated. Therefore, we hypothesized that the dietary consumption of tucum-do-cerrado ( Bactris setosa Mart.…”
Section: Introductionmentioning
confidence: 99%